Surfactin production using papaya peel aqueous extract as substrate and its application for iron adsorption (Research, Society and Development, 2020)
The presence of metals in industrial effluents has become a major environmental problem since these residues are often disposed of in lakes or rivers. Aiming to recover contaminated areas the remediation by washing using biosurfactants appears as an alternative technique that features low toxicity to the environment. This paper aims to evaluate the efficiency in iron removal within a synthetic effluent, utilizing a biosurfactant. This was produced in a bioreactor (37°C, 200 rpm, 0.5 vvm) derived from a papaya peel aqueous extract and the Bacillus subtilis UFPEDA strain 86. The fermentation tests revealed that this Bacillus is a great producer for the biosurfactant. The tests also displayed that the papaya peel extract is a viable substrate for the production of biosurfactant by this strain. Among the results found, in 24 hours of cultivation, the highest concentration of biomass and product was obtained, of 2.17 ± 0.04 g.L-1 and 2.88 ± 0.01 g.L-1, respectively. The biosurfactant provided a Critical Micellar Concentration (CMC) of 20 mg.L-1. The batch method was used in the obtainment of removal data, in which a series of solutions at different concentrations of iron ions were exposed to different amounts of biosurfactant, both raw and purified, at a temperature of 25 °C, under agitation (200 rpm) and pH ~ 6.3. A multivariate experimental design was carried out in the presence of crude and purified biosurfactant. The results demonstrated significant interactions involved for the following independent variables: concentration of iron ions, concentration of biosurfactant and the treatment time. The iron removal percentages varied between 47.2% and 95.82% in the presence of the raw biosurfactant, and between 37.01% to 91.94% in the presence of the purified surfactant. The Langmuir adsorption model was the better adjusted, providing a maximum adsorption capacity at approximately 10 mg.g-1.